Peran Money Ethics dalam Memoderasi Love Of Money dan Gender Terhadap Persepsi Etika Penggelapan Pajak - Putri, Rafelia Cahyono; Afifudin, Afifudin; Badria, Nuril (Universitas Islam Malang, 2026)
This study analyzes the moderating role of money ethics in the relationship between love of money, gender, and perceptions of tax evasion ethics. Tax evasion remains a persistent ethical issue, particularly when viewed from a behavioral perspective that emphasizes individual values and ethical judgments. Grounded in ethical and behavioral theories, this study posits that a strong orientation toward money may shape ethical perceptions, while money-related ethical values may influence this relationship. Using a quantitative approach, data were collected from 105 accounting students selected through a proportional sampling technique to ensure representative distribution across the population. The data were gathered through questionnaires and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that love of money has a positive and significant effect on perceptions of tax evasion ethics, whereas gender shows no significant effect. Furthermore, money ethics is proven to strengthen the influence of love of money on perceptions of tax evasion ethics, but it does not moderate the relationship between gender and perceptions of tax evasion ethics. These findings highlight the importance of ethical values related to money in shaping ethical perceptions and underscore the role of ethics education in accounting to mitigate unethical tax behavior.Keywords: Love of money; gender; money ethics; tax evasion ethics